The Allegorical Use of the Rituals of Hunting in Galway Kinnell's "The Bear" (Journal of the College of Languages (JCL), 2014)
Galway Kinnell (1927-) is considered as one of the most important contemporary American poets who brought about a drastic change in the American poetry of the nineteen sixties. Kinnell's poetry is characterized by being simple in style and deep in content. Poetry for him is a means through which he perceives the inner levels of consciousness in an attempt to comprehend the depths of the American self. Therefore, he writes narrative poems in which the emphasis is not on the rhetorical effects, but on the inner transformations through which the poet goes."The Bear" (1968) is typical of Kinnell's introspective poetry. It takes the form of a journey in which the rituals of hunting are used allegorically to embody the state of the spiritual progress which the hunter achieves through his metaphysical sense of the suffering of his prey. Kinnell makes use of the spiritual connotations of the techniques of the Eskimo hunters to give full expression to the fatal fight in which man has to be involved to fathom the meaning of the unfathomable.